Dual-Energy CT Enterography in Intestinal Tuberculosis: Role of Relative Enhancement Calculated on Iodine Maps in Assessing Disease Activity - Bhalla, Deeksha; Singh, Tarvinder; Bhatia, Anmol; Kalra, Naveen; Kochhar, Rakesh; Gupta, Vikas; Vaiphei, Kim (Indian Journal of Radiology and Imaging, 2025)
This article studies the role of dual-energy computed tomography (DECT) enterography with iodine material decomposition images in activity assessment of tuberculosis of the bowel.Twenty-four patients with suspected tuberculous bowel involvement were enrolled in this prospective study. All patients underwent DECT enterography as well as endoscopy and biopsy. Quantitative assessment of iodine overlay images was done to map the absolute and relative iodine uptake in involved segments of the bowel and lymph nodes. Comparison of the iodine uptake was made with histopathological activity grading using Spearman's correlation. The temporal change in the iodine uptake on posttreatment versus pretreatment group was recorded and tested for significance using Student's t-test and Wilcoxon signed rank test.Excellent correlation was found between grading of inflammatory activity on histopathology and relative bowel enhancement measured on iodine maps (Spearman's rho 0.895, p < 0.001). Attenuation values and absolute iodine uptake in the bowel showed no significant difference in the pre- and posttreatment groups (p > 0.05), while relative bowel as well as lymph nodal enhancement were significantly different (p = 0.001 and 0.008, respectively).Uptake on the iodine maps in DECT data set showed correlation with histopathology as well as posttreatment resolution, suggesting the role of DECT in disease activity assessment.
Keywords: dual-energy CT; intestine; iodine maps; lymph nodes; tuberculosis